Grammatical metaphor in English pharmaceutical discourse - Vũ, Thị Mẫu (University of Languages and International Studies, 2017)
The study is an attempt to explore grammatical metaphor in English pharmaceutical discourse from the systemic functional perspective. The framework adopted for the analysis is developed by Halliday (1985 & 1994), Halliday & Martin (1993), Thompson (1996), (...)